Cyber terrorist detection by using integration of Krill Herd and Simulated Annealing algorithms - Al-Sukhni H.A.H.; Ahmad A.B.; Madihah Mohd Saudi; Najwa Hayaati Mohd Alwi (Science and Information Organization, 2024)
Indexed by WOS/SCOPUS/ERA